Differential changes in amygdala and frontal cortex Pde10a expression during acute and protracted withdrawal - Logrip, Marian L.; Zorrilla, Eric P. (Frontiers in Integrative Neuroscience, 2014)
Alcohol use disorders are persistent problems with high recidivism rates despite repeated efforts to quit drinking. Neuroadaptations that result from alcohol exposure and that persist during periods of abstinence represent putative molecular determinants of the propensity to relapse. Previously we demonstrated a positive association between phosphodiesterase 10A (PDE10A) gene expression and elevations in relapse-like alcohol self-administration in rats with a history of stress exposure. Because alcohol withdrawal is characterized by heightened anxiety-like behavior, activation of stress-responsive brain regions and an elevated propensity to self-administer alcohol, we hypothesized that Pde10a expression also would be upregulated in reward- and stress-responsive brain regions during periods of acute (8-10 h) and protracted (6 wk) alcohol withdrawal. During acute withdrawal, elevated Pde10a mRNA expression was found in the medial and basolateral amygdala, as well as the infralimbic and anterior cingulate subdivisions of the medial prefrontal cortex, relative to alcohol-naïve controls. The basolateral amygdala was the only region with elevated Pde10a mRNA expression during both acute and protracted withdrawal. In contrast to the elevations, Pde10a mRNA levels tended to be reduced during protracted withdrawal in the dorsal striatum, prelimbic prefrontal cortex, and medial amygdala. Together these results implicate heightened PDE10A expression in the basolateral amygdala as a lasting neuroadaptation associated with alcohol dependence.